Correlation of magnetic resonance imaging findings and arthroscopy findings in diagnosis of intra articular ligament injuries of knee joint - Chintapalli, Surya Sri Karun; Thekkada, Pavith Janardhan (International Journal of Research in Orthopaedics, 2023)
Background: The knee is the largest synovial joint in body with extra and intra articular ligaments which act as supporting structures around the joint. The intra articular ligaments of knee are more commonly injured. An accurate and early diagnosis of the internal derangement of knee is necessary for planning the treatment. In this study we compare the findings of magnetic resonance imaging (MRI) with arthroscopy and evaluate the accuracy of MRI in diagnosing intra-ligament injuries of knee. Methods: It is a prospective study conducted in the department of orthopaedics, Raja Rajeswari medical college and hospital, Bangalore from July 2018 to May 2021. Selection criteria include 80 patients who presented with history of ligamentous injury to the knee. The MRI was obtained and selected cases were posted for arthroscopic surgery after obtaining the informed consent. The MRI findings and Arthroscopy findings were correlated and statistical data analysis is prepared to obtain accuracy of MRI. Results: In this study 80 patients were selected and data was prepared. ACL tear presented with 100% sensitivity and 95% accuracy, PCL injuries shows 100% sensitivity and 97% accuracy, medial meniscus tears presented with sensitivity 96.15% and accuracy 95%, lateral meniscus tears presented with sensitivity 95.83% and accuracy 97.50% of MRI. Conclusions: In our study the MRI has more capable in detecting anterior horn tears, multiple tears and underneath tears that may be overlooked in arthroscopy. However, appropriate sequences, analysed in different planes, newer techniques, powerful tomograms will improve the diagnostic accuracy and reduce errors.